Afmeting excl. passe-partout. . Titel prent: Eendracht maakt macht. . Op de achterzijde van de tekening staat een schets - Hahn, Albert,
Afmeting excl. passe-partout. Titel prent: Eendracht maakt macht. Op de achterzijde van de tekening staat een schets.